Navigating Metabolism - Navdeep S. Chandel (Cold Spring Harbor Laboratory Press, 2015)
"Metabolic pathways used to be "road maps" most biologists learned as undergraduates and then promptly forgot. Recent work has revealed how changes in metabolism are closely linked to many aspects of cell behavior and the development of cancer and other diseases. This book represents both a new look at metabolism and a refresher course. It surveys the major metabolic pathways, places these in biological context, and highlights the key control points that control cell behavior and can become dysregulated in disease"